Composite‐rotating consensus of multi‐agent systems with a leader and nonuniform delays. Issue 4 (28th December 2018) - Mo, Lipo; Jiang, Yixuan
Abstract: This paper focuses on the composite‐rotating consensus problem of second‐order multi‐agent systems with a leader and nonuniform time‐delays. First, a distributed control law is proposed to solve this problem. Second, by using the complex frequency domain analysis method, the maximal upper bound of time‐delays is deduced and it is proven that all agents eventually rotate around a common point while this point rotates around the origin, provided all communication time‐delays are less than the the maximal upper bound of time‐delays. Finally, simulation results are provided to demonstrate the effectiveness of the theoretical results.